2020
DOI: 10.3319/tao.2020.06.08.01
|View full text |Cite
|
Sign up to set email alerts
|

Updates to the on-land seismogenic structure source database by the Taiwan Earthquake Model (TEM) project for seismic hazard analysis of Taiwan

Abstract: To provide information towards understanding Taiwan's earthquake hazard and risk, the multidisciplinary Taiwan Earthquake Model (TEM) project, supported by the Ministry of Sciences and Technology, had prepared and published a first version of seismic hazard assessment maps of Taiwan in 2016, together with an on-land seismogenic structure database of the island. In the years following the publication of this first version, we have constructed an updated version of this database. Seven structures were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…This rate accounts for only 50% of the GNSS‐based value, meaning that some structures may have to take up twice or more shortening than average. It is possible that a large fraction of the remaining shortening is absorbed by a few major structures near the deformation front, such as the offshore extension of the Chishan and the Youchang fault (Shyu et al., 2020), and even the deformation front itself (Lacombe et al., 2004). The exact amount of shortening across each of these anticlines is beyond the scope of this study, and yet this study provides a workflow to realize such an analysis in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate accounts for only 50% of the GNSS‐based value, meaning that some structures may have to take up twice or more shortening than average. It is possible that a large fraction of the remaining shortening is absorbed by a few major structures near the deformation front, such as the offshore extension of the Chishan and the Youchang fault (Shyu et al., 2020), and even the deformation front itself (Lacombe et al., 2004). The exact amount of shortening across each of these anticlines is beyond the scope of this study, and yet this study provides a workflow to realize such an analysis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Leveling survey and InSAR analysis also show rapid ground uplift over some proposed diapiric anticlines, at rates of 18-37 mm/yr (Ching et al, 2016;Tsukahara & Takada, 2018). Despite the popularity of attributing anticlinal deformation to mud diapirism in southwestern Taiwan, studies reveal a significant influence of active fault systems in this area's geology and geomorphology (e.g., Y.-G. Chen & Liu, 2000;Gong et al, 1996Gong et al, , 1998Hsieh & Knuepfer, 2001;Liu et al, 2021;Mouthereau et al, 2001;Shyu et al, 2005Shyu et al, , 2016Shyu et al, , 2020. Disagreement therefore exists regarding whether the anticlinal structures are caused by mud diapirism, or whether they are simply fault-related folds (e.g., Biete et al, 2018;S.-T. Huang et al, 2004;Lacombe et al, 1999).…”
Section: 1029/2022tc007234mentioning
confidence: 99%
“…An update could include outcomes of the Reevaluation of Probabilistic Seismic Hazard of Nuclear Facilities in Taiwan Using SSHAC Level 3 Methodology. Although we have updated the seismogenic structure database based on state-of-the-art geomorphology and geology studies (Shyu et al, 2020), we will incorporate seismogenic parameters obtained from geodetic research. In respect to the GMPEs, some new sets of GMPEs, for example, Chao et al (2020) and Phung et al (2020), will be discussed, and their epistemic uncertainties (Phung et al, 2019) will be evaluated and considered in a logic tree.…”
Section: Discussionmentioning
confidence: 99%
“…The TEM PSHA2015 implemented the seismogenic structure database summarized by Shyu et al (2016), which incorporated 38 seismogenic structures with planar geometries and characteristic magnitudes, that is, a single magnitude and fixed recurrence interval for each structure. This database was updated (Shyu et al, 2020) to include six newly identified structure sources: the Chushiang, Gukeng, Tainan frontal, Longchuan, Youchang and Fengshan hills frontal structures (ID 39–44, respectively; corresponding fault alignment of each source is presented in Figure 1a). Also, based on additional evidence, such as seismic profiles, dip angles of some sources are suggested to be depth variable, with a gentler dipping at depth (Table 1).…”
Section: Modification Of Seismogenic Structure Sourcesmentioning
confidence: 99%
“…S1). Among (Cheng 1997), 1986-1992(Kao et al 1998Jian et al, 2018a, b), where blue lines indicate active faults (Shyu et al, 2020) them, the 1951 sequence includes three strong earthquakes (M ~ 7) struck the Hualien region on the same day (Cheng et al 1997). These earthquakes also triggered another two major events one hundred kilometers to the south in November 1951 (Cheng et al 1997;Chen et al 2008;Chung et al 2008).…”
Section: Introductionmentioning
confidence: 99%